2023
DOI: 10.1186/s12913-023-09188-y
|View full text |Cite
|
Sign up to set email alerts
|

Change in glycaemic control with structured diabetes self-management education in urban low-resource settings: multicentre randomised trial of effectiveness

Abstract: Background In high-resource settings, structured diabetes self-management education is associated with improved outcomes but the evidence from low-resource settings is limited and inconclusive. Aim To compare, structured diabetes self-management education to usual care, in adults with type 2 diabetes, in low-resource settings. Research design and methods. Design Single-blind randomised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 27 publications
(42 reference statements)
0
14
0
Order By: Relevance
“…[ 21 ] A multicenter RCT conducted in an urban low-resource setting by Lamptey R et al . [ 29 ] studied the association between structured DSME and glycemic control. They found that structured DSME was not associated with a change in HbA1C at follow-up in low-resource settings.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] A multicenter RCT conducted in an urban low-resource setting by Lamptey R et al . [ 29 ] studied the association between structured DSME and glycemic control. They found that structured DSME was not associated with a change in HbA1C at follow-up in low-resource settings.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the included studies are reported in Table 1. Of the 44 studies, 21 were conducted in upper-middle-income countries , 21 in lower-middle-income countries [1,38,[72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90], and two were conducted in low-income countries [91,92], as grouped by the World Bank criteria [41]. The studies were conducted in diabetes clinics or hospitals (n = 15 [34%]), public or private hospitals/clinics (n = 21[48%]) and community settings/home-based locations (n = 8 [18%]).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Five trials used DM self-management-based coaching programmes [54,67,80,89,91], four trials used the empowerment approach and interactive teaching model [63,64,74,76], and three used the theory of self-efficacy as a theory or model to underpin intervention content [65,66,68]. Each of the following models was used by one trial only: the beliefs, attitudes, subjective norms and enabling factors (BASNEF) model [72]; the predisposing, reinforcing and enabling constructs in educational diagnosis and evaluation (PRECEDE) model [78]; the chronic care model [58]; clinic-based intensified diabetes management model (C-IDM) [60]; the healthbelief model [81]; the comprehensive systematic health education and promotion (SHEP) model [85]; the diabetes comprehensive care model (DCCM) [88]; the structured DSME model [38] and the lifestyle intervention holistic model (LIHM) [90]. The remaining 23 trials Approximately 73% (n = 32) of the interventions were delivered using a face-to-face format, 20% (n = 9) utilising face-to-face intervention with telephone follow-up and 7% (n = 3) using a remotely delivered text message/web-based intervention.…”
Section: Intervention Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations